2017
DOI: 10.1371/journal.pcbi.1005501
|View full text |Cite
|
Sign up to set email alerts
|

Temperature–amplitude coupling for stable biological rhythms at different temperatures

Abstract: Most biological processes accelerate with temperature, for example cell division. In contrast, the circadian rhythm period is robust to temperature fluctuation, termed temperature compensation. Temperature compensation is peculiar because a system-level property (i.e., the circadian period) is stable under varying temperature while individual components of the system (i.e., biochemical reactions) are usually temperature-sensitive. To understand the mechanism for period stability, we measured the time series of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 51 publications
3
31
0
Order By: Relevance
“…Mean expression levels of all four reporters changed with temperature in a very similar manner, with low expression levels at the extremes (18°C and 29°C) and higher expression levels at 21°C and 25°C ( Figure S4 , Table S1 ), precluding any meaningful correlation between protein levels and transcription rates as was the case for the halteres. It has previously been reported that luciferase activity is temperature dependent, either increasing or decreasing with temperature (e.g., Kurosawa et al., 2017 ; McElroy and Seliger, 1961 ). Although we cannot rule out direct effects of temperature on luciferase activity, we do not observe consistent changes of luciferase activity with temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Mean expression levels of all four reporters changed with temperature in a very similar manner, with low expression levels at the extremes (18°C and 29°C) and higher expression levels at 21°C and 25°C ( Figure S4 , Table S1 ), precluding any meaningful correlation between protein levels and transcription rates as was the case for the halteres. It has previously been reported that luciferase activity is temperature dependent, either increasing or decreasing with temperature (e.g., Kurosawa et al., 2017 ; McElroy and Seliger, 1961 ). Although we cannot rule out direct effects of temperature on luciferase activity, we do not observe consistent changes of luciferase activity with temperature.…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been reported that luciferase activity is temperature-dependent, either increasing or decreasing with temperature (e.g. (Kurosawa et al, 2017;McElroy and Seliger, 1961)). Although we cannot rule out direct effects of temperature on luciferase activity, we do not observe consistent changes of luciferase activity with temperature.…”
Section: Peripheral Clocks In the Antennae Slow Down With Increasing mentioning
confidence: 98%
“…Even this condensed network contains 17 regulations constituting multiple negative and positive feedback loops ( 13 ). To generate self-sustained oscillations, negative feedback loops are essential ( 14 , 15 ). Originally, the self-inhibitions of the period and cryptochrome genes have been considered as the primary negative feedback loops ( 16 ).…”
Section: Introductionmentioning
confidence: 99%